Penerapan Model Pembelajaran Problem Besed Learning Mata Kuliah Elektronika Digital pada Mahasiswa Teknik Elektro Universitas Negeri Padang - Suryadi, Irfan Tri; Sukardi, Sukardi (Lembaga Yasin AlSys, 2024)
The low learning outcomes of electrical engineering students, especially in the cognitive domain, are caused by a lack of student activity in class and being embarrassed to ask questions if the material presented is not understood by students. Based on the results of observations carried out in the Department of Electrical Engineering, it was found that the learning model was more teacher-centred (TCL) so that there were no varied learning models implemented in the learning process. Therefore, it is necessary to provide a variety of learning models so that they can generate good enthusiasm, cognitive, affective and psychomotor skills in a learning process, so that a Besed Learning learning model can be used as an innovative learning model and train students' ability to solve problems well. in order to improve good learning outcomes and psychomotor skills for 2TEIB electrical engineering class students at universitas negeri padang. The aim of this research is to determine the application of the Problem Based Learning learning model in digital electronics courses to electrical engineering students at Padang State University. This research uses a quantitative type of research, this research uses a 1 class design using pre-test and post-test to determine the results of the implementation of the problem-based learning model, as well as the population in the research, namely Random Sampling, where the population in the sample that will be studied is class 2TEIB majoring in electrical engineering, For sampling, the probability sampling technique was used.The results of the analysis can be seen from the application of the problem-based learning model which was carried out well, as well as getting the average value of the pretest and posttest results for the 2TEIB class. The results were good, namely the posttest results were higher than the pretest results because after implementing the problem-based learning model good and perfect, the use of the problem-based learning model provides a significant difference as evidenced by the results of hypothesis testing using SPSS version 24, data obtained namely sig (0.001) < 0.05, so that Ha is accepted and Ho is rejected.